GABA Shunt in Durum Wheat - Carillo, Petronia (Frontiers in Plant Science, 2018)
Plant responses to salinity are complex, especially when combined with other stresses, and involve many changes in gene expression and metabolic fluxes. Until now, plant stress studies have been mainly dealt only with a single stress approach. However, plants exposed to multiple stresses at the same time, a combinatorial approach reflecting real-world scenarios, show tailored responses completely different from the response to the individual stresses, due to the stress-related plasticity of plant genome and to specific metabolic modifications. In this view, recently it has been found that γ-aminobutyric acid (GABA) but not glycine betaine (GB) is accumulated in durum wheat plants under salinity only when it is combined with high nitrate and high light. In these conditions, plants show lower reactive oxygen species (ROS) levels and higher photosynthetic efficiency than plants under salinity at low light. This is certainly relevant because the most of drought or salinity studies performed on cereal seedlings have been done in growth chambers under controlled culture conditions and artificial lighting set at low light. However, it is very difficult to interpret these data. To unravel the reason of GABA accumulation and its possible mode of action, in this review, all possible roles for GABA shunt under stress are considered, and an additional mechanism of action triggered by salinity and high light suggested.